2016
DOI: 10.5897/ajar2016.11356
|View full text |Cite
|
Sign up to set email alerts
|

Root spatial distribution in coffee plants of different ages under conservation management system

Abstract: Root system growth and soil structure are interdependent and the threshold of separation between both of them is complex. However, by the evaluation of soil pore space, it is possible to characterize the root system growth environment. The aim of this study was to evaluate the effect of conservation management system over time on pore distribution and on root system development of coffee plantation in Cerrado Oxisol, located in the state of Minas Gerais, Brazil. Two coffee plantation areas were sampled (3 or 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Silva et al [8] found a significant volume of inter-aggregate pores (macropores) after 3 years of coffee cultivation in Latosols, confirming the benefits of the management system using deep preparation associated with surface gypsum application. In the layer between 0.20-0.40 m of the soil, even after 5 years of cultivation, Silva [20] also found that soil management favored the expressive increase of pore volume of classes 9.0-2.9, 2.9-0.6 and 0.6-0.2 μm (mesopores), which is relevant since a good portion of the water retained in the soil will be available to the plants.…”
Section: Coffee -Production and Researchmentioning
confidence: 85%
See 4 more Smart Citations
“…Silva et al [8] found a significant volume of inter-aggregate pores (macropores) after 3 years of coffee cultivation in Latosols, confirming the benefits of the management system using deep preparation associated with surface gypsum application. In the layer between 0.20-0.40 m of the soil, even after 5 years of cultivation, Silva [20] also found that soil management favored the expressive increase of pore volume of classes 9.0-2.9, 2.9-0.6 and 0.6-0.2 μm (mesopores), which is relevant since a good portion of the water retained in the soil will be available to the plants.…”
Section: Coffee -Production and Researchmentioning
confidence: 85%
“…Particularly in Latosols under this management system, it was observed that in the absence of chemical and physical limitations of the soil the coffee root system reached depths greater than 1 m at 3 years of age (Figure 3), which is of fundamental importance to ensure crop survival in periods of edaphic drought [8].…”
Section: Coffee -Production and Researchmentioning
confidence: 96%
See 3 more Smart Citations